Corona and financial stability 4.0: Implementing a european pandemic equity fund - Arnoud W. A. Boot; Elena Carletti; Hans-Helmut Kotz; Jan Pieter Krahnen; Loriana Pelizzon; Marti G. Subrahmanyam (Leibniz Institute for Financial Research SAFE, 2020)
This Policy Letter presents a proposal for designing a program of government assistance for firms hurt by the Coronavirus crisis in the European Union (EU). In our recent Policy Letter 81, we introduced a new, equity-type instrument, a cash-against-tax surcharge scheme, bundled across firms and countries in a European Pandemic Equity Fund (EPEF). The present Policy Letter 84 focuses on the principles and conditions relevant for the operationalization of a EPEF. Our proposal has several desirable features. It: a) offers better risk sharing opportunities, augmenting the resilience of businesses and EU economies; b) is need-based, thereby contributing to an effective use of resources; c) builds on conditions and credible controls, addressing adverse selection and moral hazard; d) is accessible to smaller and medium-sized firms, the backbone of Europe's economy; e) applies Europe-wide uniform eligibility criteria, strengthening support among member states; f) is a scheme of limited duration, reducing (perceived) government interference in businesses; g) creates a template for a growth-oriented public policy, aligning public and private sector interests; and h) builds on the existing institutional infrastructure and requires minimal legislative adjustments.
urn:nbn:de:hebis:30:3-534475
Keywords: 330; Coronavirus; Equity fund; Financial stability; Policy measures in the EU; Risk sharing